PENGARUH PENERAPAN MEDIA PUZZLE KATA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS I SDN 124386 PEMATANGSIANTAR - Mia Naftalia Napitupulu; Desi Siajabat; Sukardo Sitohang (STKIP Subang, 2026)
This study was motivated by the low learning outcomes of first-grade students in Indonesian language at SDN 124386 Pematangsiantar, which were caused by teacher-centered instruction and the limited use of engaging learning media. The study aimed to determine the effect of word puzzle media on students' Indonesian language learning outcomes. This research employed a quantitative approach using an experimental method with a One Group Pretest–Posttest Design. The sample consisted of 22 first-grade students selected through total sampling. Learning achievement tests were administered before and after the treatment. The collected data were analyzed using normality, homogeneity, and t-tests. The results indicated that students' average learning outcomes improved after the implementation of the word puzzle media. The hypothesis testing showed that the calculated t-value (15.54) was higher than the t-table value (2.08) at a significance level of 0.05, indicating that the alternative hypothesis was accepted. These findings demonstrate that the use of word puzzle media has a significant positive effect on Indonesian language learning outcomes among first-grade students at SDN 124386 Pematangsiantar. The implementation of word puzzle media enhanced students' engagement, motivation, and participation during the learning process, leading to improved academic achievement.